Plumbagin suppresses epithelial to mesenchymal transition and stemness via inhibiting Nrf2-mediated signaling pathway in human tongue squamous cell carcinoma cells - Pan ST; Qin Y; Zhou ZW; He ZX; Zhang X; Yang T; Yang YX; Wang D; Zhou SF; Qiu JX (Dove Medical Press, 2015)
Shu-Ting Pan,1 Yiru Qin,2 Zhi-Wei Zhou,2,3 Zhi-Xu He,3 Xueji Zhang,4 Tianxin Yang,5 Yin-Xue Yang,6 Dong Wang,7 Shu-Feng Zhou,2 Jia-Xuan Qiu1 1Department of Oral and Maxillofacial Surgery, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 2Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 3Guizhou Provincial Key Laboratory for Regenerative Medicine, Stem Cell and Tissue Engineering Research Center and Sino-US Joint Laboratory for Medical Sciences, Guiyang Medical University, Guiyang, Guizhou, People’s Republic of China; 4Research Center for Bioengineering and Sensing Technology, University of Science and Technology Beijing, Beijing, People’s Republic of China; 5Department of Internal Medicine, University of Utah and Salt Lake Veterans Affairs Medical Center, Salt Lake City, UT, USA; 6Department of Colorectal Surgery, General Hospital of Ningxia Medical University, Yinchuan, Ningxia, People’s Republic of China; 7Cancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, People’s Republic of China Abstract: Tongue squamous cell carcinoma (TSCC) is the most common malignancy in oral and maxillofacial tumors with highly metastatic characteristics. Plumbagin (5-hydroxy-2-methyl-1, 4-naphthoquinone; PLB), a natural naphthoquinone derived from the roots of Plumbaginaceae plants, exhibits various bioactivities, including anticancer effects. However, the potential molecular targets and underlying mechanisms of PLB in the treatment of TSCC remain elusive. This study employed stable isotope labeling by amino acids in cell culture (SILAC)-based quantitative proteomic approach to investigate the molecular interactome of PLB in human TSCC cell line SCC25 and elucidate the molecular mechanisms. The proteomic data indicated that PLB inhibited cell proliferation, activated death receptor-mediated apoptotic pathway, remodeled epithelial adherens junctions pathway, and manipulated nuclear factor erythroid 2-related factor 2 (Nrf2)-mediated oxidative stress response signaling pathway in SCC25 cells with the involvement of a number of key functional proteins. Furthermore, we verified these protein targets using Western blotting assay. The verification results showed that PLB markedly induced cell cycle arrest at G2/M phase and extrinsic apoptosis, and inhibited epithelial to mesenchymal transition (EMT) and stemness in SCC25 cells. Of note, N-acetyl-l-cysteine (NAC) and l-glutathione (GSH) abolished the effects of PLB on cell cycle arrest, apoptosis induction, EMT inhibition, and stemness attenuation in SCC25 cells. Importantly, PLB suppressed the translocation of Nrf2 from cytosol to nucleus, resulting in an inhibition in the expression of downstream targets. Taken together, these results suggest that PLB may act as a promising anticancer compound via inhibiting Nrf2-mediated oxidative stress signaling pathway in SCC25 cells. This study provides a clue to fully identify the molecular targets and decipher the underlying mechanisms of PLB in the treatment of TSCC. Keywords: PLB, SILAC, EMT, stemness, Nrf2, tongue squamous cell carcinoma